2005
DOI: 10.17660/actahortic.2005.678.7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Use of Various Amaryllidaceae Plants Against Alzheimer's Disease

Abstract: Alzheimer's Disease (AD), a slowly progressive neuropsychiatric illness, principally characterized by memory deficits, has become the fourth leading cause of death in developed nations. Since the patients with AD suffer from marked reduction of cholinergic neuronal function resulting in a deficiency in acetylcholine (ACh) concentration in the brain, and these reductions are associated with impairments in memory, cholinergic enhancement strategies have been at the forefront of efforts to palliate pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Most of the compounds having potential anticholinesterase activity are isolated from Buxaceae, Amaryllidaceae, Lycopodiaceae, Lamiaceae, Chenopodiaceae, Papaveraceae, Apocynaceae , and Labiatae species. [ 13 17 18 25 27 29 45 59 ] Following are three of the imporant families having potential compounds to be used as anticholonesterase inhibitors.…”
Section: Anticholinesterase Phytochemical Classesmentioning
confidence: 99%
“…Most of the compounds having potential anticholinesterase activity are isolated from Buxaceae, Amaryllidaceae, Lycopodiaceae, Lamiaceae, Chenopodiaceae, Papaveraceae, Apocynaceae , and Labiatae species. [ 13 17 18 25 27 29 45 59 ] Following are three of the imporant families having potential compounds to be used as anticholonesterase inhibitors.…”
Section: Anticholinesterase Phytochemical Classesmentioning
confidence: 99%
“…The acetyl-cholinesterase inhibiting rates were: lycorine 43.69%, tazettine 36.34%, galanthamine 48.00%, 3epihydroxybulbispermine 30.18% N-nor-galanthamine 34.09% and haemanthamine 20.8 %. Chloroform: methanol extract and crude alkaloid extract of the plant were also possessed acetyl-cholinesterase inhibiting activity (46.62±0.77 and 46.96±0.08%, respectively) (98)(99) .…”
Section: Narcissus Tazettamentioning
confidence: 97%
“…Rhee et al (2003) showed that the methanol extract of G. nivalis had 96% inhibition against AChE (Rhee et al, 2003). Chloroform:methanol (1 : 1) extracts of the bulbs of G. elwesii and G. ikariae inhibited AChE at 73.18 and 75.56% (10 μg/ml), comparable to the alkaloid extracts at 77.23 and 76.96% (10 μg/ml) (Orhan and S ¸ener, 2005). Phytochemical study of alkaloid extract of G. ikariae yielded amaryllidaceae-type alkaloids, including lycorine (IC 50 3.16 µM), tazettine, crinine, galanthamine (IC 50 3.2 µM), 3-epi-hydroxybulbispermine and 2demethoxymontanine.…”
Section: Anticholinesterase Activitymentioning
confidence: 98%